PATHOGENICITY OF ISOLATES OF ENTOMOPATHOGENIC FUNGI TO WORKERS OF Acromyrmex heyeri (Forel, 1899) (HYMENOPTERA: FORMICIDAE) - Saldanha, Mateus Alves; Costa, Ervandil Corrêa; Muniz, Marlove Fátima Brião; Quevedo, Alexsandra Cezimbra; Pedron, Leandra; Sarzi, Janaina Silva (Floresta, 2023)
Leaf-cutting ants stand out among the main pests of agricultural and forestry crops. Chemical control is the most used method to control these insect pests, requiring the development of techniques that are less harmful to the environment. The present study aimed at verifying the action of Beauveria bassiana (Bals.) Vuill, Cordyceps fumosorosea (Wize), and Metarhizium anisopliae (Metsch.) Sorokin isolates on the in vitro mortality of Acromyrmex heyeri (Forel). Seven isolates of entomopathogenic fungi were used: three isolates of Beauveria bassiana (IBCB 66, IBCB 170, and IBCB 632), one isolate of Cordyceps fumosorosea (IBCB 130), and three isolates of Metarhizium anisopliae (IBCB 348, IBCB 383, and IBCB 425), and five concentrations of spores (1.0×104, 1.0×105, 1.0×106, 1.0×107, and 1.0×108 spores mL-1) for each fungal isolate. The control treatment consisted of autoclaved distilled water and 0.01% Tween 40, without fungal pathogens. The experiments were carried out in a completely randomized design with five replications. Estimation of lethal concentrations of LC50 and LC90 was performed using Probit analysis. The isolates of B. bassiana, C. fumosorosea, and M. anisopliae were pathogenic to leaf-cutting ants with the five tested concentrations of spores. Higher mortality of the specimens was reached with increasing concentration. The entomopathogenic fungi evaluated in this study proved to be efficient agents for the biological control of Acromyrmex heyeri.